Assessment of Knowledge, Attitude and Practices Regarding the Nutritional Needs of Pregnant Women - Neha Palous; Ateeqa Khan; Kousar Parveen; Rubia Jabeen (Sustainable Business and Society in Emerging Economies)
Purpose: The aim of this study was to assess the knowledge, attitude, and practices regarding the nutritional needs of pregnant women.